Intensity variations of geomagnetic field in Santa Maria (Brazil) over the past 3 thousand years - Frigo, Everton (2018)
Earth magnetic field variations at secular scales and at hundred quilometers have internal origin at the outer core. The most important feature associated with this internal field is the South Atlantic Magnetic Anomaly (SAMA), which covers the South America and it is characterized by the lowest total field intensity at the surface. Here, we investigate the geomagnetic field variations in Santa Maria (Brazil) over the past 3 ka. Results indicate that the intensities observed in Santa Maria are the lowest of the geomagnetic field over the past 3 ka. The consequences of these field features could be the increase in the electrically charged particles reaching the low Earth atmosphere that may generate problems in the communications systems or climate changes.